Serum carnitine concentration and the acyl to free carnitine ratio in nondialysis chronic kidney disease and hemodialysis patients. Issue 1 (31st March 2021) - Daimon, Shoichiro; Yasuda, Miyuki; Nishitani, Mitsuhiro
Abstract: Mechanisms of impaired fatty acid metabolism may not be the same in nondialysis and hemodialysis patients. Correlations between the serum‐free carnitine concentration (FC), acylcarnitine concentration (AC), acyl to free carnitine ratio (AC/FC), and estimated glomerular filtration rate (eGFR) in the nondialysis population and the duration of hemodialysis in hemodialysis patients were investigated. As the eGFR decreased, the FC and AC increased, and as the duration of hemodialysis became longer, the FC and AC decreased. The AC/FC increased consistently as the eGFR decreased and the duration of hemodialysis increased. As an exception, the AC/FC decreased in the patients with a hemodialysis duration less than 90 days, which was not explained by carnitine removal by hemodialysis. In nondialysis patients, a functional, rather than an absolute, carnitine deficiency is a main cause of impaired fatty acid metabolism. Long‐term hemodialysis exacerbates absolute carnitine deficiency, whereas hemodialysis treatment may improve impaired fatty acid metabolism.